2000
DOI: 10.1080/713659326
|View full text |Cite
|
Sign up to set email alerts
|

Accidental and deliberate overdose among opiate addicts in methadone maintenance treatment: are deliberate overdoses systematically different?

Abstract: The frequency of accidental or deliberate overdose was investigated among 200 opiate addicts in methadone substitution treatment in clinics in Edinburgh and south London. One hundred and three of the participants reported a mean of 3.4 overdoses, with 71 (69%) reporting that their most recent overdose was accidental, 27 (26%) deliberate—the remainder were uncertain. Those whose last overdose was deliberate were more likely to have been prescribed diazepam at that time and were more depressed at the time of int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 16 publications
1
30
2
Order By: Relevance
“…Many of the studies conducted to date have not explored the meaning of deliberate or intentional to the individual, [5][6][7]10 and most (including this study) categorize overdoses as intentional or otherwise on the basis of a dichotomous question. Suicidal thought and behavior are complex, and it is possible that more sensitive questioning could reveal some level of suicidal intent, while dichotomous questioning may reveal none.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Many of the studies conducted to date have not explored the meaning of deliberate or intentional to the individual, [5][6][7]10 and most (including this study) categorize overdoses as intentional or otherwise on the basis of a dichotomous question. Suicidal thought and behavior are complex, and it is possible that more sensitive questioning could reveal some level of suicidal intent, while dichotomous questioning may reveal none.…”
Section: Discussionmentioning
confidence: 99%
“…Best et al 7 found that 65% who reported a deliberate overdose had been in treatment at the time, compared to only 35% who said their overdose was accidental. Furthermore, those who reported a deliberate overdose were more likely to be depressed, but no more anxious than other participants.…”
Section: Intentional Overdosementioning
confidence: 99%
See 3 more Smart Citations